The fiscal consequences of deflation : evidence from the golden age of globalization - Afonso, António (2016)
We study the fiscal consequences of deflation on a panel of 17 economies in the first wave of globalization, between 1870 and 1914. By means of impulse response analyses and panel regressions, we find that a 1 percent fall in the price level leads to an increase in the public debt ratio of about 0.23- 0.32 pp. and accounting for trade openness, monetary policy and the exchange rate raises the absolute value of the coefficient on deflation. Moreover, the public debt ratio increases when deflation is also associated with a period of economic recession. For government revenue, lagged deflation comes out with a statistically significant negative coefficient, while government primary expenditure seems relatively invariant to changes in prices.